MODIFICATION OF WOVEN DENDROCALAMUS ASPER IN COMPOSITE APPLICATIONS - Raharjo, Rudianto; Darmadi, Djarot Bangun; Gapsari, Femiana; Setyarini, Putu Hadi; Alamsyah, Fikrul Akbar (International Journal of Mechanical Engineering Technologies and Applications, 2024)
The aim of this study is to examine the influence of immersing Petung Bamboo in a NaOH solution on the tensile strength (TS) of composites containing an epoxy matrix. Petung Bamboo Webbing was given 0%, 3%, 6% and 9%, soaking treatment. The Composite utilised in this investigation was fabricated by the Vacuum Assisted Resin Infusion technique. Tensile testing of composites is conducted according to the ASTM D638-1 standard. The findings indicated a positive correlation between the concentration of NaOH immersion and the adhesion between the woven surface of Petung Bamboo and the matrix. Consequently, the TS of the Composite was enhanced. However, increasing the concentrations beyond a certain point leads to more degradation of the lignin and cellulose in the fibers, resulting in a loss in the strength of the composite. The Petung Bamboo woven reinforced Composite achieved the highest TS of 136.06 MPa after being treated with a 6% NaOH immersion. This was followed by a 3% NaOH immersion treatment resulting in a TS of 106.04 MPa. Without any NaOH immersion treatment, the composite had a TS of 97.31 MPa. The lowest TS of the composite was observed after a 9% NaOH immersion treatment, measuring 90.79 MPa. The Petung Bamboo wicker-reinforced composite with NaOH immersion treatment showed higher fiber pullout and fiber-matrix debonding failures, while higher NaOH treatment concentration reduced these failures.